RECOGNIZING COERCIVE CONTROL: A LEGISLATIVE MODEL FOR OVERCOMING THE CHALLENGES OF FIGHTING INVISIBLE DOMESTIC ABUSE - Marina Tallman (Washington University Journal of Law and Policy, 2024)
This Note advocates for amending civil codes addressing domestic abuse to incorporate coercive control as a recognized form of violence. Coercive control is an emotional domestic abuse that is not always visible or physical but was realized on a larger scale after victims were forced into confinement with abusers during COVID-19 lockdowns. The United States legal system, in comparison to its international peers, has very rarely engaged in legislative discussion on coercive control. Much of the debate regarding domestic abuse in the form of coercive control has been purely academic and without implementation in a meaningful number of jurisdictions. This Note identifies the needs of state legislators to respond to the non-recognition of coercive control in domestic abuse laws by pursuing legal reform accompanied by comprehensive, illustrative definitions that establish clear behavioral markers, and further suggests the development of guidance materials for lawmakers and judiciaries to facilitate the implementation of a model statute. Further, state legislators provided with guidance from international predecessors to navigate the obstacles to implementation that are in place when the legal concept of abuse is expanded to recognize coercive control by either codification or criminalization.
Keywords: COVID-19; Domestic Abuse; Coercive Control